Retraction Note: Heisenberg-type uncertainty principle for the second \(q\)-Bargmann transform on the unit disk - Akram, Nemri (CUBO, A Mathematical Journal, 2025)
The Editor-in-Chief and the Managing Editor of CUBO, A Mathematical Journal, have decided to retract this article, in accordance with the Ethics Statement of the journal. The article was submitted on September 8th, 2024, and it was scheduled to appear in vol. 27, no. 1, pp. 55–73, 2025. After this manuscript was already been published online in CUBO’s webpage, the original referee of the article informed the editorial team that a very similar article had been recently published on the Communications of the Korean Mathematical Society, vol. 40, no. 2, pp. 291–302, 2025. DOI: https://doi.org/10.4134/CKMS.c240150. After a careful analysis of both manuscripts, the editorial team concluded that this was an instance of self-plagiarism. Even though the titles are diﬀerent, the results, techniques and discussion in both manuscripts are almost identical. It is important to stress that the manuscript was accepted for publication in CUBO on March 20th, 2025, and it was accepted in the CKMS on February 18th, 2025. This situation is completely anomalous. The Editor-in-Chief of the CKMS has been informed. The author has not responded to us regarding this retraction.